Enhancing Key Digital Competence in Pre-service Kindergarten Teachers: A Design-Centered SPOC Blended Learning Model - Lu, Lingming; Sitthiworachart, Jirarat; Petsangsri, Sirirat (My University, 2025)
As our world becomes increasingly digital, educators must possess strong digital skills to effectively prepare their students for the future. However, traditional teacher education programs often neglect the cultivation of digital competence. To address this gap, this study developed a Design-Centered SPOC Blended Learning (DCSBL) model to enhance the digital competence of pre-service kindergarten teachers. The DCSBL model integrates elements of blended learning, design-based learning, and digital competency training strategies. A quasiexperimental study was conducted to evaluate the effectiveness of this model. The results indicated that the experimental group, which received DCSBL instruction, significantly outperformed the control group in terms of digital skills achievement (DSA) and Self-evaluation of key digital competence (KDC). Furthermore, qualitative analysis of student reflections revealed that DCSBL stimulated students’ learning motivation, engagement, and sense of achievement. However, the study also highlighted the increased cognitive load and meta-cognitive demands associated with the DCSBL Model. To realize the full potential of competency-based education, teaching assessment must be reformed. The development of digital competence for teachers should be combined with a “micro-certification” system. This approach can provide a more flexible and personalized pathway for educators to acquire and validate their digital skills.
Keywords: design-centered SPOC blended learning model; key digital competence; pre-service kindergarten teachers; quality education; small private online course